2015
DOI: 10.1534/g3.115.018796
|View full text |Cite
|
Sign up to set email alerts
|

Identification of QTLs for Rust Resistance in the Peanut Wild Species Arachis magna and the Development of KASP Markers for Marker-Assisted Selection

Abstract: Rust is a major pathogen of the peanut crop. Development and adoption of rust-resistant cultivars is the most cost efficient and effective way to control the spread of the disease and reduce yield losses. Some cultivated peanut germplasm accessions have a degree of resistance, but the secondary gene pool is a source of much stronger resistance alleles. Wild species, however, have undesirable agronomic traits that are a disincentive to their use in breeding. The identification of genomic regions that harbor dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
60
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(64 citation statements)
references
References 47 publications
4
60
0
Order By: Relevance
“…RLPs are significantly enriched in A08 (Figure a), which may result from frequent rearrangement events between A08 and A07 . QTLs are associated with resistance regions of nematode resistance, root‐knot nematode (RKN) (Meloidogyne arenaria (Neal) Chitwood) resistance, rust resistance, and late leaf spot resistance . Interestingly, we found 14 QTLs close to RGA‐enriched regions (Table S17, Supporting Information).…”
Section: Resultsmentioning
confidence: 90%
“…RLPs are significantly enriched in A08 (Figure a), which may result from frequent rearrangement events between A08 and A07 . QTLs are associated with resistance regions of nematode resistance, root‐knot nematode (RKN) (Meloidogyne arenaria (Neal) Chitwood) resistance, rust resistance, and late leaf spot resistance . Interestingly, we found 14 QTLs close to RGA‐enriched regions (Table S17, Supporting Information).…”
Section: Resultsmentioning
confidence: 90%
“…Since peanut rust ( Puccinia arachidis ) was not consistently found in the field, detached leaf assays were conducted as described by Leal‐Bertioli et al. () using rust uredospores collected from infested field‐grown susceptible plants. Resistance was evaluated as incubation period, total number of lesions, and sporulating lesions per leaf area.…”
Section: Methodsmentioning
confidence: 99%
“…Consequently, the inheritance of traits related to oil components, as well as other agronomically important traits, is very complex. Over the last decade, genetic studies of peanut have advanced greatly: DNA markers were developed (Pandey et al, 2012); molecular genetic maps were established (Gautami et al, 2012; Shirasawa et al, 2013); and quantitative trait loci (QTL) were identified for agronomically important traits including oil components (Shirasawa et al, 2012; Leal‐Bertioli et al, 2015; Kolekar et al, 2016). These resources can be used as tools for DNA marker‐assisted selection to accelerate breeding programs in peanut as in other crop species (Perez‐de‐Castro et al, 2012).…”
mentioning
confidence: 99%